Serum Zinc and Copper in Children with Febrile Seizures in Basrah,Iraq - aljabere, sawsan issa; Jaber, Basher Abdullah (Journal of the Faculty of Medicine Baghdad, 2019)
Background:Trace elements are essential micronutrients that exist in very low concentrations in the body. They play an important role in various physiological processes and are crucial for proper functioning of the immune system. Many studies have shown that some micronutrients may have a role in febrile seizure such as selenium, zinc and copper. objectives :To determine the level of serum zinc and copper in children with febrile seizures and explore their relation to selected patients’ variables. Methods: The study included 66 infants and children with simple febrile seizures with two control groups;a febrile control group which includes (62) children with febrile illnesses who were admitted to emergency department at Basrah Maternity and Children Hospital and Basrah General Hospital from the 1st of March to the end of October 2013, and ahealthy control group which includes ( 58) children. Serum zinc and copper ere measured for all infants and children enrolled in the study. Results: Patients with febrile seizure had a significantly lower mean serum zinc level (8.85 ±3.26) in comparison to febrile patients and healthy children (14.98 ±2.20), (13.33 ±1.99) respectively. There is no significant association between the level of serum zinc and selected variables.S erum copper level did not show a significant difference between patients with febrile seizures and control groups. Conclusion: Zinc supplementation may be considered in children who are at risk of recurrent febrile seizure .